The Impact of Iron Deficiency Anemia on Histomorphological Features of Placenta and the New Born Infants - Rafah Hady Lateef Al-Mamouri (Journal of Global Pharma Technology, 2018)
Iron deficiency anemia during pregnancy is  mutual heamatological disorder that happens in pregnancy, it affects maternal blood , leading to hypoxia, which cause changes in the structure of the placenta . Aim of study to explore the changes occurres both   in gross morphology and in histology of the placenta in anemic mothers. Methods: A fifty placentas were taken from mothers (full term) delivered at hospital constituted the material for the  present study. Full term placenta  was collected with case history and investigated after delivery of fetus. Two cm pieces were removed from both anemic and normal  group of placenta fixed in 10% formalin and used for processing and staining.  The microscopic study revealed histomorphological abnormalities as increased capillaries per villas, thickening of capillary basement membrane , trophoblastic basement  membrane, cytotrophoplastic proliferation,syncytial knots and fibrosis. All these changes occurred maintaining sufficient efficiency of placenta, to fulfill demand of oxgen in the fetus.Key words: anemia, histology, placenta,pregnancy.